Sosialisasi Dan Edukasi Ekonomi Syariah Untuk Pelajar: Fondasi Kuat Menuju Kesejahteraan Dan Keadilan Berbasis Syariah Di Sma It Al-Utsaimin Bangkinang - Zakir, Muhammad; Winario, Mohd; Mairiza, Diany; Khairi, Rifqil; Irmawanti, Irmawanti (Journal of Community Sustainability, 2025)
This community service activity was carried out for students of SMA IT Al-Utsaimin Bangkinang, Riau Province, where the purpose of this community service is to provide provisions in increasing understanding of the concept of Sharia Economics to the community, especially generation Z of students of SMA IT Al-Utsaimin Bangkinang. The methods used in this community service activity are through counseling and presentation, discussion and practice (pretset and post test) for participants. The counseling method is used to explain the importance of knowing the concept of Sharia economics for students in order to become prosperous generations using sharia principles. The presentation method is used to show a work process, namely the stages of how we can become individuals who have a prosperous economy. While the question and answer method is used to give participants the opportunity to consult in understanding further the material that has been given. The practice method is used to see how far the participants understand the service before and after the material is delivered. The availability of adequate experts in delivering this material, the enthusiasm of the participants, and the support of the principal for the implementation of the activity are supporters of the implementation of this PPM activity. The obstacles faced are that the students do not yet have initial knowledge about the material of the concept of Islamic economics and limited time in delivering the material. The results of this service indicate that: The community service program can be organized well and run smoothly according to the activity plan that has been prepared, the results of this service concluded that: First, Most students of SMA IT Al-Utsaimin do not understand the concept of Islamic economics well, Second, The achievement of the objectives of the community service program for students of SMA IT Al-Utsaimin Bangkinang, the entire program that has been carried out with collaboration between the school and the community service have been carried out all and in accordance with the event rounddown and the time that has been determined previously.